Tinjauan Hukum Terhadap Sengketa Peralihan Hak Milik Atas Tanah Melalui Perjanjian Tukar Menukar - Zefanya, Dewa Gede Jeremy; Utari, A.A. Sri (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 03 (2022)DO - 10.24843/AC.2022.v07.i03.p13, 2022)
The purpose of this study is to determine the regulation of legal protection against the transfer of ownership rights to land through an exchange agreement and to understand the factors that influence the occurrence of default on the transfer of property rights to land through an exchange agreement. The writing of this scientific paper uses normative legal research methods. The object of this legal research is based on the existence of an Empty Norm. The approach used in this paper uses a legal approach, a conceptual approach. The application of the principle of light and cash in the exchange agreement where the land object is in two different areas has not been properly accommodated. Government Regulation Number 24 of 2016 has not accommodated technical rules regarding the form of implementing instructions and a form of technical guidance that explicitly regulates the exchange agreement whose land objects are in two different areas or between regions. The factor that causes a default in the transfer of property rights to land through an exchange agreement is based on the absence of clear legal rules that accommodate technical rules regarding the form of implementing instructions and technical instructions that explicitly regulate exchange agreements. the existence of legal certainty and order in the community, the state is very interested in regulating both control and regarding the transfer or transfer of land rights in Indonesia.